Isolasi Bakteri dari Kuda Laut (Hippocampus barbouri) - Indra Gandhi Ahmad; Hilal Anshary; Sriwulan Sriwulan (Fakultas Pertanian Universitas Samudra, 2023)
Captive breeding of seahorses (Hippocampus barbouri) which is a follow-up of their activities in the exploitation of natural large - scale does not escape from the problems of the disease. Gills and kidneys are the main target of the inspection. Wet mount is one way of checking the disease. This study aims to look at other forms of bacteria isolated from the gills and kidney seahorse (H. barbouri) morphologically. Media used are media Zobell Marine Agar (ZMA) and Thiosulphate Citrate Bile Salts Sucrose Agar (TCBSA) then be isolated bacteria with a pillowcase technique spread to see koloi dominant bacteria. more dominant bacteria grow dimurinikan back with scratch method (streak). The result of five isolates (isolates A, B, C, D and E) were predominantly found growing on media ZMA, two isolates (isolates B and C) not found growing on media TCBSA. Overall bacteria in media and TCBSA ZMA has the form round colonies and smooth-edged. TCBSA media can not be found on the bacterial colonies that fluoresce.